Principal to Principal: Conversations in Servant Leadership and School Transformation - Wallace, Rocky (Rowman & Littlefield Publishers, 2008)
Principal to Principal: Conversations in Servant Leadership and School Transformation takes the reader into the real world of school leadership, as a retiring elementary principal and his successor engage in a 12-month mentoring partnership. Packed with emotion and the complexities of the twenty-first century school, the story weaves in and out of the day-by-day transformation that can take place when past paradigms and traditions are challenged, and students are put first. The unleashed potential of the servant leadership model, and the critical importance of core values, vision, and strategic change are addressed with passion and intensity as the two colleagues discover together how fast a school can really change_if the human resources are all focused on the same goal: creating a great school that meets the variety of needs of every child it serves_no exceptions.